Qualidade fisiológica e expressão de peroxirredoxinas em sementes de coffea arabica submetidas à secagem e ao armazenamento - Ribeiro, Thamires Lopes (2020)
The low longevity of Coffea arabica seeds has also been attributed to their sensitivity to desiccation. Thus, understanding the physiological aspects of these seeds during the drying process and during storage is of great importance, since the quality of the seeds influences the vigor of the seedlings used to form the crops. The objective of this research was to evaluate the physiological quality and the expression of the 1-Cys PRX protein in coffee seeds submitted to drying and storage, aiming at the establishment of drying methods associated with the water content of the seeds to preserve the quality of the seeds during storage. Seeds of Coffea arabica L. from the cultivar Catuaí Amarelo (IAC 62) produced on the Bom Jardim farm located in Bom Sucesso, Minas Gerais, were used. The fruits were harvested at the cherry ripening stage and peeled. The seeds went through the process of natural degumming and pre-dried up to 46% water content. Afterwards, the seeds were dried until reaching the water content of 40%, 20% and 10% and later stored for 60, 120 and 180 days in a cold room (10 ± 2oC and 70% RH). Seeds with 46% water content and no storage were used as a control treatment. The physiological quality of the seeds was evaluated by first germination test, germination test, normal seedlings at 30 days of sowing test, cotyledonary leaves expanded at 45 days of sowing test, emergence test and rate of emergence (IVE). The expression of the 1-Cys PRX protein was also evaluated by the Western Blot technique. The evaluations were carried out at four periods, before seed storage and after 60, 120 and 180 days of storage. Reduced vigor was observed in seeds dried at 10% water content. Higher expression of the PRX protein was verified in dried coffee seeds up to 20% and 10% water content during storage and there was no expression of the protein in seeds with 46% water content (control treatment) and in dried seeds at 40% water content after 60 days of storage. It can be concluded that the physiological quality of Coffea arabica seeds is influenced by the water content and storage period. Using the Western Blot technique, it was possible to detect greater expression of the peroxiredoxin protein in dried coffee seeds up to 20 and 10% water content. There is a reduction in the vigor of the seeds when they are dried, mainly up to 20 and 10% of water content.